Handbook of Salamanders : The Salamanders of the United States, of Canada, and of Lower California - Bishop, Sherman C. (Sherman Chauncey), 1887-1951 (Book collections on Project MUSE., 1994)
Despite their abundance in many parts of North America, salamanders have generally been neglected by all but a few specialists. In this book--first published in 1943--Sherman C. Bishop discusses in a lively but authoritative manner the 126 species and subspecies of salamanders that are known to exist in the United States, Canada, and Baja California. Group by group, Bishop describes salamanders in accounts that give the common and technical names, type of locality, range, habitat, size, anatomical characteristics, color, breeding habits, and relationships--all in a uniform arrangement that makes the handbook especially convenient for studying both living animals and laboratory specimens. His brief introduction surveys the relationships and general habits of salamanders and gives information on collecting and preserving them. In his foreword to the 1994 reprint edition, Edmund D. Brodie, Jr., a specialist on salamanders, updates the taxonomy of the group. Annotation Published: March 2014.